Insights of Outcome after Resection of Small Nonfunctioning Neuroendocrine Pancreatic Tumors - Estela Regina Ramos Figueira; Julia Fray Ribeiro; Thiago Costa Ribeiro; Ricardo Jureidini; Guilherme Naccache Namur; Thiago Nogueira Costa; Telesforo Bacchella; Ivan Cecconello (Gastroenterology Research and Practice)
Background. The incidence of small nonfunctioning neuroendocrine pancreatic tumors (NF-PNETs) has been increasing systematically in the last few decades. Surgical resection was once considered the treatment of choice but has been questioned in the direction of a more conservative approach for selected patients. Our aim was to analyze the outcome of surgical resection of small (≤3cm) NF-PNETs. Methods. We retrospectively evaluated 14 patients with sporadic NF-PNETs who underwent pancreatic resection. Data were collected from patients’ medical records. Results. Of the 14 patients included, 35.71% were men, and the average age was 52.36±20.36 years. Comorbidities were present in 92.86% of the cases. The incidence of postoperative complications was 42.86%, the 30-day mortality was zero, and the length of follow-up was 3.31±3.0 years. The results of pathological evaluations revealed WHO grade I in 42.86% of cases, II in 21.43%, and neuroendocrine carcinoma in 35.71%. The median tumor size was 1.85cm (range, 0.5–3cm), and 2 cases had synchronous metastasis. The median TNM stage was IIa (range, I–IV). The disease-free and patient survival rates were 87.5% and 100% at 3 years and 43.75% and 75% at 10 years, respectively. The tumor pathological grade was significantly higher in head tumors than body-tail tumors, but there were no differences with respect to tumor size and TNM staging. Conclusion. A surgical approach to treat small sporadic NF-PNETs is safe with low mortality and high patient survival. Based on these data, small pancreatic head tumors can be more aggressive, suggesting that surgical resection is still the best option to treat small nonfunctioning PNETS. Thus, conservative treatment should be indicated very cautiously for only cases with absolute contraindications for surgery.